Legal Issues Arising from Client-Driven Variation Claims in Construction Contracts - Zulkefly, Nur Anis Nadhirah; Ismail, Zulhabri (Journal of Technology Management and Business, 2026)
Variation claims are an almost inevitable feature of construction contracts due to the dynamic and complex nature of construction projects. Under the context of variation claims, it generally arise when a contractor is required to execute the work that is outside of the contract parameters and in return, proposes a compensation in terms of time or cost. Among these, variations initiated by clients frequently give rise to legal disputes, particularly in relation to entitlement, procedural compliance, valuation, and dispute resolution. This research examines the legal issues arising from client-driven variation claims in construction contracts, with a specific focus on how such claims are interpreted and resolved within the Malaysian legal framework. Adopting a doctrinal legal research methodology, this study analyses statutory provisions, standard forms of construction contracts, namely the PWD Form 203A, PAM Contracts 2018, and FIDIC Contracts 2017, and a comprehensive selection of recent Malaysian court decisions. Through systematic case law analysis, the research identifies key legal issues underpinning client-driven variation claims, including the classification of works as variations, entitlement to variation payments, procedural non-compliance with contractual requirements, and the role of adjudication under the Construction Industry Payment and Adjudication Act 2012 (CIPAA). The study further examines the repercussions of such variation claims on contractors, particularly in terms of loss of entitlement, financial disruption, exposure to liquidated ascertained damages, failure to recover loss and expense, and prolonged dispute resolution. The findings reveal that courts consistently emphasise strict adherence to contractual procedures, especially regarding written instructions, timely notices, and proper documentation. While judicial decisions demonstrate an effort to balance contractual certainty with commercial realities, contractors who fail to comply with procedural requirements often face adverse outcomes despite the substantive merits of their claims. This research contributes to construction law scholarship by clarifying prevailing legal principles governing client-driven variation claims and highlighting the practical implications of judicial reasoning for contractors. The study also provides useful guidance for industry practitioners in managing variation claims and mitigating legal risks arising from client-initiated changes in construction projects.